A scenario for the emergence of protoviroids in the RNA world and for their further evolution into viroids and viroid-like RNAs by modular recombinations and mutations. Issue 1 (15th January 2022) - Flores, Ricardo; Navarro, Beatriz; Serra, Pedro; Di Serio, Francesco
Abstract: Viroids are tiny, circular, and noncoding RNAs that are able to replicate and systemically infect plants. The smallest known pathogens, viroids have been proposed to represent survivors from the RNA world that likely preceded the cellular world currently dominating life on the earth. Although the small, circular, and compact nature of viroid genomes, some of which are also endowed with catalytic activity mediated by hammerhead ribozymes, support this proposal, the lack of feasible evolutionary routes and the identification of hammerhead ribozymes in a large number of DNA genomes of organisms along the tree of life have led some to question such a proposal. Here, we reassess the origin and subsequent evolution of viroids by complementing phylogenetic reconstructions with molecular data, including the primary and higher-order structure of the genomic RNAs, their replication, and recombination mechanisms and selected biological information. Features of some viroid-like RNAs found in plants, animals, and possibly fungi are also considered. The resulting evolutionary scenario supports the emergence of protoviroids in the RNA world, mainly as replicative modules, followed by a further increase in genome complexity based on module/domain shuffling and combination and mutation. Such a modular evolutionary scenario would have facilitated the inclusion in the protoviroid genomes of complex RNA structures (or coding sequences, as in the case of hepatitis delta virus and delta-like agents), likely needed for their adaptation from the RNA world to a life based on cells, thus generating the ancestors of current infectious viroids and viroid-like RNAs. Other noninfectious viroid-like RNAs, such as retroviroid-like RNA elements and retrozymes, could also be derived from protoviroids if their reverse transcription and integration into viral or eukaryotic DNA, respectively, are considered as a possible key step in their evolution. Comparison of evidence supporting a general and modular evolutionary model for viroids and viroid-like RNAs with that favoring alternative scenarios provides reasonable reasons to keep alive the hypothesis that these small RNA pathogens may be relics of a precellular world.